Wealth Effects - Patrick Legros; Andrew F. Newman (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
We construct a general equilibrium model of firm formation in which organization is endogenous. Incentive-based wealth effects arises from lower bounds on wealth and utility, and these affect the way in which different organizational forms can divide the proceeds of production. Individuals may choose between organizaing their firms as hierarchies or as partnerships; these decisions are mediated by agency costs in both labor and financial markets. The type of organization which emerges depends on the distribution of wealth and need not be surplus maximizing: the same output could be produced with less labor if some firms were forced to reorganize from their equilibrium form. This result suggests that instead of serving to provide incentives efficiently, organizations may sometimes act to transfer surplus from some agents to others, at potential social cost.
Keywords: 330